Implementation of Character Education Through Pancasila Subjects at Taman Rahayu 04 Setu State Elementary School - Yessa Afrilia; Senja Pertiwi; Sarah Nahila Zaini (CV. Rayyan Dwi Bharata, 2023)
This study aims (1) to find out the implementation of character education, the obstacles to the implementation process and the solutions to the process of implementing character education through Pancasila education subjects at SDN Taman Rahayu 04 Setu. This type of research is descriptive qualitative at SDN Taman Rahayu 04 Setu with school heads and homeroom teachers as well as grade VI students at SDN Taman Rahayu 04 Setu. The research focus is on the character of discipline, courtesy, hard work, responsibility and honesty in class VI at SDN Taman Rahayu 04 Setu. The data sources used are primary data sources in the form of interview results and secondary data sources in the form of documents. Data collection techniques used are interview techniques, observation, and documentation. The results of this study indicate that (1) the implementation of character education through Pancasila education subjects at SDN Taman Rahayu 04 Setu is carried out by the teacher through three stages, namely the planning, implementation and assessment stages (2) as for the inhibiting factors experienced by the teacher in implementing character education, namely: , lack of student awareness in: complying with regulations, student motivation to learn and student awareness of duties and responsibilities (3) efforts made by teachers to overcome these obstacles, namely by setting an example for time discipline and obeying rules, paying equal attention to all students and give punishment to students who break the rules.